CLINICAL AND MORPHOLOGICAL CHARACTERISTICS OF AN ARTOFACIAL VAGINA FORMED FROM THE COLON (LITERATURE REVIEW) (World Bulletin of Public Health, 2022)
The article is devoted to the clinical and morphological characteristics of the transformation of the epithelial walls of the artificial vagina. The researchers note that the study of literature data indicates that the clinical and morphological criteria for the transformation of the epithelial walls of the artificial vagina created from the sigmoid colon are not sufficiently developed. The existing information in scientific publications is very diverse and not systematized. It is noted that the majority of scientific researches are given in foreign sources. At the same time, there is an increase in the frequency of appeals of citizens about this pathology.